Guidelines for hospital nephrology assistance from the Brazilian Society of Nephrology (BSN) - Mauricio Younes-Ibrahim; Eduardo Rocha; Thiago Reis; Vinícius Sardão Colares; Emerson Quintino de Lima; Lucia da Conceição Andrade; Eduardo Cantoni Rosa; Helen Siqueira Cardoso; Fernando Thomé; Daniela Ponce; José H. Rocco Suassuna; Luis Yu (Brazilian Journal of Nephrology)
Abstract The AKI Department of the Brazilian Society of Nephrology (BSN) has prepared a hospital nephrology assistance guide, which encompasses the aspects involved in the nephrologist's role in caring for patients with kidney diseases within the hospital setting. The guide addresses the following main topics: 1) the role of the nephrologist in hospital care; 2) non-dialysis kidney support therapy; 3) technical standards for hospital dialysis care; and 4) outpatient follow-up of patients with acute kidney injury/disease. It provides a detailed description of the nephrologists' main responsibilities, their role in both non-dialysis and dialysis hospital care, as well as describing all available dialysis methods, the required infrastructure, human resources, and records of these procedures. The guide concludes with recommendations for the outpatient follow-up of nephrological patients after hospital discharge. The primary purpose of this BSN guide is to provide support for a better medical and multidisciplinary assistance for nephrologists and other professionals involved in the hospital patient’s nephrology care.